FUNCTIONS OF DISTRIBUTIONS OF AMOUNTS OF UNIFORALLY DISTRIBUTED RANDOM VALUES OF TIMES OF PROCESSING THE REQUEST OF THE INFOCOMMUNICATION SYSTEM - Babich, M.Yu.; Butaev, M.M.; Tarasov, A.A.; Ivanov, A.I; Malygin, A.Yu.; Sauanova, K.T.; Sagyndykova, Sh.N. (Academic Scientific Journal of Computer Science, 2020)
The normal distribution of a random variable is usually used in studies of the probabilistic properties of information systems. Using the normal distribution to approximate the distributions determined over a bounded distorts the physical meaning of the model and the numerical results obtained can only be used as an initial approximation. The purpose of the work is to improve methods for calculating the probability properties of infocommunication systems. The object of study is an analytical method for calculating the request processing time in the system, the subject is the formula for calculating the duration of sequential processing of a request by elements of the system with uniformly distributed independent random processing times. For positive random variables, it is proposed to use finite-interval distribution laws, for example, beta distribution. Density formulas and probability functions for the sums of two, three, and four independent randomly distributed variables are given.